2016
DOI: 10.1112/blms/bdw055
|View full text |Cite
|
Sign up to set email alerts
|

The discriminant 10 Shimura curve and its associated Heun functions

Abstract: The Shimura curve of discriminant 10 is uniformized by a subgroup of an arithmetic (2,2,2,3) quadrilateral group. We derive the differential structure of the ring of modular forms for the Shimura curve and relate the ring generators to explicit Heun functions for the quadrilateral group. We also show that the Picard–Fuchs equation of the associated family of abelian surfaces has solutions that are modular forms. These results are used to completely describe the exceptional sets of the Heun functions, and we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In [1], it is shown that the exceptional set of the hypergeometric function 2F1false(124,524,34,tfalse) is in a one to one correspondence with the isogeny class of a certain elliptic point. Similarly it is shown in [2] that the exceptional set of the Heun function H(272,736,112,712,23,12;t) is also represented by an isogeny class. We now show that this phenomenon is more general.…”
Section: Applicationssupporting
confidence: 59%
See 2 more Smart Citations
“…In [1], it is shown that the exceptional set of the hypergeometric function 2F1false(124,524,34,tfalse) is in a one to one correspondence with the isogeny class of a certain elliptic point. Similarly it is shown in [2] that the exceptional set of the Heun function H(272,736,112,712,23,12;t) is also represented by an isogeny class. We now show that this phenomenon is more general.…”
Section: Applicationssupporting
confidence: 59%
“…Thus, if γ t is any loop on E t varying continuously in t, then p(t) = γt ω t is a solution to the Picard-Fuchs equation 4t(t − 1)D 2 p(t) + (8t − 4)Dp(t) + p(t) = 0. This is a hypergeometric differential equation, and its monodromy group is isomorphic to the congruence group Γ (2). Moreover, if we choose t = λ(z), the Legendre modular function, then it can be shown that this differential equation has ϑ 2 3 (z) as a solution, where ϑ 3 (z) is a particular theta function [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation